2015
DOI: 10.1007/s00586-015-4359-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability among clinicians diagnosing low back-related leg pain

Abstract: Purpose To investigate agreement and reliability among clinicians when diagnosing low back-related leg pain (LBLP) in primary care consulters. Methods Thirty-six patients were assessed by one of six physiotherapists and diagnosed as having either leg pain due to nerve root involvement (sciatica) or referred leg pain. Assessments were video recorded. In part one, the physiotherapists each viewed videos of six patients they had not assessed. In part two, videos were viewed by another six health professionals. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…There is no ‘gold standard’ for the diagnosis of sciatica and it is, effectively, a clinical diagnosis where the clinician considers the pain is coming from a lumbar nerve root. As with all clinical diagnoses, the threshold for diagnosing sciatica may vary between clinicians [ 39 ]. An MRI showing nerve root compression should not be taken to confirm the diagnosis of sciatica but is simply one further piece of evidence that a clinician may take into account.…”
Section: Discussionmentioning
confidence: 99%
“…There is no ‘gold standard’ for the diagnosis of sciatica and it is, effectively, a clinical diagnosis where the clinician considers the pain is coming from a lumbar nerve root. As with all clinical diagnoses, the threshold for diagnosing sciatica may vary between clinicians [ 39 ]. An MRI showing nerve root compression should not be taken to confirm the diagnosis of sciatica but is simply one further piece of evidence that a clinician may take into account.…”
Section: Discussionmentioning
confidence: 99%
“…Patients excluded from the analysis were cases where clinicians indicated low diagnostic confidence, irrespective of either a referred leg pain or sciatica diagnosis. A reliability study, nested in this cohort, showed good reliability on diagnosis of LBLP when clinician confidence is high (at least 80%) [ 4 ]. Diagnostic uncertainty is a clinical reality as sometimes a return visit from the patient is needed to further confirm or explore diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of sciatica for model (i) reference standard was when the clinician documented the presence of leg pain was due to sciatica and they were ≥ 80% confident in their diagnosis. A cut off point of ≥ 80% diagnostic confidence was used because at this criterion, reliability among clinicians diagnosing LBLP improves considerably [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients expressing interest in participating in the trial proceed to have a standardised assessment for sciatica by the physiotherapist, to establish full eligibility and ascertain subgroup allocation. Eligibility for the trial is based on the assessing physiotherapist being ≥70% confident of a diagnosis of sciatica [27]. Patients who have leg pain thought by the assessing physiotherapist to be due to causes other than sciatica are excluded (for example: referred leg pain, hip pathology, peripheral neuropathy, vascular pain), as are patients for whom there is substantial diagnostic uncertainty.…”
Section: Recruitment Proceduresmentioning
confidence: 99%